Comments on the molecular mechanism of acoustic wave propagation in simple liquids - KUCZERA, Franciszek; GMYREK, Joachim (Archives of Acoustics, 1989)
When seeking an explanation for the molecular mechanism of acoustic wave propagation in liquids it was stated that theoretical considerations applying the Lennard—Jones type expression for energy can not serve this purpose. A certain molecular interpretation of the ABL principle is proposed as a solution. On this path we obtain an expression for propagation velocity of an acoustic wave in terms of space filling a relationship between sound velocity and coefficient of viscosity and an expression for intermolecular compressibility.